The Gait Analysis of Locomotor Disorders. Cineradiographic Assessment of the Efficacy of G-II of Brace for Severe OA of the Knee - FUJITA Masaaki; IKAWA Yoshinori; KAWAI Masayuki; MOTOKAWA Tetsu; CHIBA Koji (Japanese Journal of National Medical Services, 1999)
Patients with severe knee osteoarthritis (OA) who can't be anesthetized because of severe general condition have to select the orthosis. Efficacy of G- II OA brace for such patients has been recommended. We evaluated dynamic characteristics of this orthosis by cineradiography. Five patients on or off-brace stood in front of the image tube of cineradiography system and were required to step with their toes on the floor. Twenty-forty pictures of the knee every 1/30 minutes during heel-on to off were measured at 5 points of medial eminentia and bilateral edges of the tibia and femur. We obtained instabilities of lateral thrust in the fluctuation of the eminentia, medial subluxation of the femur in the distance between medial border of the tibia and femur. In the condition of offbrace these instabilities increased according of the lord.Three cases on-brace showed the reposition of the femur and the increase of lateral thrust.Dynamic study of the severe OA of the knee by cineradiography revealed that G-II OA brace gave reposition of medial joint. These will be one of the factor that knee pain is subsided. 目的: 中・高度OA膝に有効なG-IIOA装具に対し, 足踏み動作時の膝運動の動的評価をシネラジオグラフィー法(足踏みシネ)で行いその特性をみた. 対象と方法: OA膝5例に対し, G-IIOA装具装着時と非装着時の膝運動を足踏みシネで評価した. 3歩分を1/30秒毎に撮影し, 側方亜脱臼と側方動揺性を計測した.結果: 側方亜脱臼は装具装着により整復され, 側方動揺性は5例中症例状の改善した8例で大きくなることがわかった.考察: 装具なしでは, 内側関節の小面積で荷重伝達をしていたが装具装着により外側動揺が大きくなり, 内側関節の整復が得られ, 荷重伝達面積が増加したため疼痛軽減ができたと推察した. またOA膝の疼痛発生の要因には側方動揺性と側方亜脱臼が大きく関与していることが示唆された.